PENGARUH PROFESIONALISME TENAGA PENDIDIK DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PRAJURIT PADA AKADEMI TNI - Joucelin Alaida Panese (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
The leadership expects the professionalism of work to be better, it is really expected because if the professionalism of the work is good, it will greatly affect the level of work performance of soldiers. Work motivation is to provide encouragement and effort to achieve the satisfaction of the desires and goals of each soldier. Satisfaction is meant to feel pleasure or happiness when a desire has been achieved. This soldier's work performance is the result of work within the scope of his responsibility, of course referring to a formal and structured system that is used as an instrument to measure, assess, and influence work-related characteristics. While the objectives of this research are: to determine the effect of the professionalism of educators and work motivation on the work performance of soldiers at the TNI Academy.“The sampling technique used in this study the author uses the Random Sampling technique or randomly. Some soldiers are the population and 89 people are sampled using the Slovin formula in Husein Umar (2012).“The results obtained that partially and simultaneously there is a positive and significant influence between the Professionalism of Educators and Work Motivation on Soldier's Work Achievement.